CONTEMPORARY APPROACH TO AUTOLOGOUS BREAST RECONSTRUCTION IN ONCOLOGICAL PATIENTS: A LITERATURE REVIEW - Jadwiga Kleinrok; Hubert Kostka; Damian Dolata; Adrian Zagórski; Anna Bereta-Kostaś; Rafał Kuśmider; Małgorzata Leśnik; Patrycja Wierzbowska (International Journal of Innovative Technologies in Social Science, 2025)
Breast cancer still stands as the most frequently diagnosed cancer among women globally. The increasing prevalence of breast cancer is closely linked to the rising demand for breast reconstruction surgery following oncological treatments. This study aims to synthesise modern understanding of the autologous reconstructive techniques in breast cancer patients based on literature reviews, including meta-analyses published from 2020 to 2025. In the review, three major aspects were identified: considerations of surgical timing and its implications, outcomes of autologous versus alloplastic reconstruction, and operative techniques, comprising tissue flaps and fat grafting. Study showed emerging data relevant to timing concerning oncological interventions like radiotherapy and chemotherapy. Studies focused on inter-method comparison provided varying results in regard to patient-reported outcome measures, complication statistics, and long-term aesthetic evaluations. The review also included all known autologous approaches but concentrated on fat grafting and the latest research on adjunctive measures and safety concerning optimisation. Final aesthetic refinement methods were discussed as well. Recent studies show the outcomes of autologous breast reconstruction are positive, however more research needs to be done due to methodological caveats and contradicting outcomes. More advanced technologies are being implemented in the field, and in order to determine the best options and stratification process for patients, more focus on high-quality research is a necessity.